Do documented records and retrospective reports of childhood maltreatment similarly predict chronic inflammation? - Osborn, Meg; Widom, Cathy Spatz (Psychological medicine, 2020)
Childhood adversities have been associated with chronic inflammation and risk for cardiovascular disease. With some exceptions, existing knowledge of this relationship is based on retrospective self-reports, potentially subject to recall bias or memory problems. We seek to determine whether childhood maltreatment is associated with higher C-reactive protein (CRP) later in life and whether individuals with official and retrospective self-reports of maltreatment and men and women show similar increases in risk. Data are from in-person interviews in 2009-2010 with 443 offspring (mean age = 23.4) of parents in a longitudinal study of the consequences of childhood maltreatment. Official reports of maltreatment were abstracted from 2011-2013 Child Protective Services records. Eleven measures were used to assess self-reported maltreatment retrospectively. Seventeen percent of offspring had official reports, whereas self-reported prevalence rates ranged from 5.4% to 64.8%. CRP was assessed through blood spot samples. Regression models were used to estimate the effect of maltreatment on inflammation, adjusting for age, sex, race, parent occupational status, current depression, smoking, and heavy drinking. Individuals with official reports of child maltreatment and, specifically, physical abuse, had significantly higher levels of CRP than non-maltreated individuals. Maltreated females showed elevated CRP, independent of control variables, whereas no significant association was observed in males. Retrospective self-report measures of child maltreatment did not predict elevated CRP. Individuals with documented histories of childhood maltreatment are at increased risk for chronic inflammation and may benefit from targeted interventions. The results strengthen inferences about the effects of childhood maltreatment on inflammation in females.